Experiential learning of robotics fundamentals based on a case study of robot-assisted stereotactic neurosurgery - Faria, Carlos (2016)
Robotics has been playing an important role in modern surgery, especially in procedures that require extreme precision, such as neurosurgery. This paper addresses the challenge of teaching robotics to undergraduate engineering students, through an experiential learning project of robotics fundamentals based on a case study of robot-assisted stereotactic neurosurgery. The project was integrated into the curriculum of a Biomedical Engineering and Electrical and Computer Engineering program, but can also be integrated in related courses. First, students are given a presentation on the planning and execution of a stereotactic neurosurgery procedure, with special attention being paid to the concepts involved, namely spatial transformations, kinematics, and trajectory planning. Students are then taught to use a robotics simulation tool for robot-assisted stereotactic neurosurgery. They are shown how this can be used as a specialized control application, providing direct feedback on the robot's motion in a neurosurgery scenario. They are then required to select a robotic manipulator, and to develop and implement its control code to make it perform as a robot assistant in this surgical procedure. Project efficacy was evaluated through student self-report data (with dedicated anonymous surveys) and through the impact on academic and pedagogical results (by means of statistical inference). The results of the student surveys show that the robotics simulator for stereotactic neurosurgery is well suited to its role as an experiential learning tool since it enhances the understanding and application of several robotics concepts in an appealing manner. The positive impact of the project learning experience is supported by a comparison to earlier years of student grades, pass rates, and feedback from an institutional survey.